The protective effect of hederagenin on renal fibrosis by targeting muscarinic acetylcholine receptor. Issue 4 (1st April 2022) - Yang, Wei; He, Lijuan
ABSTRACT: Hederagenin (HE) plays a protective role by inhibiting cell proliferation and ameliorating fibrosis. The current therapy for Chronic kidney disease (CKD) often result in the risks of side effects. The present study aimed to explore whether it can protect against renal fibrosis and unveil the underlying mechanism. Transforming growth factor (TGF)-β was used to induce the fibroblasts NRK-49 F for the simulation of renal fibrosis. The cell viability and expression of fibrosis-related proteins in TGF-β-treated NRK-49 F cells was, respectively, measured by Cell Counting Kit-8 (CCK-8) and western blot. After predicting the target genes of HE, M3 receptor was measured in NRK-49 F cells treated with TGF-β alone or in combination with HE. Then, M3 receptor was silenced in TGF-β-treated NRK-49 F cells for the detection of its role in proliferation and fibrosis. Muscarinic acetylcholine receptor M3 (M3 receptor) agonist pilocarpine was further added to determine the role of M3 receptor involved. HE inhibited the proliferation and fibrosis of TGF-β-treated NRK-49 F cells. M3 receptor was predicted to be a target of HE. Moreover, interference of M3 receptor improved the proliferation and fibrosis of TGF-β-treated NRK-49 F cells. Further addition of pilocarpine reversed the inhibitory effect of HE on proliferation and fibrosis of TGF-β-treated NRK-49 F cells. HE protects against renal fibrosis in NRK-49 F cells by targeting Muscarinic acetylcholine receptor, which will provide theoretical basis for the clinical use of HE for kidney-related disease treatment. GRAPHICAL ABSTRACT: uf0001